Effect of Zoledronate on the Responses of Osteocytes to Acute Parathyroid Hormone - Kuroshima, Shinichiro (2013)
The bone anabolic effect of parathyroid hormone (PTH) therapy is blunted when used in patients who were previously on bisphosphonate treatment. Osteocytes may play a role in the bisphosphonate silencing effect on PTH therapy since bisphosphonates have been shown to reach the lacuno-canalicular system. In vivo osteocyte studies pose a significant challenge. For the current study, we developed a simple method to isolate RNA from the cortical bone enriched with osteocytes. Our purpose was to investigate how zoledronate (ZA) treatment modulates the responses of osteocytes and the bone marrow (BM) to an acute PTH treatment. Mice received ZA treatment for 3 months and a single PTH injection prior to euthanasia. Bone was histomorphometrically evaluated. Gene expression was assessed at the RNA level in osteocytes and BM. Endothelial progenitor cells (EPCs) and γδT-cells were analyzed in the BM and blood using flow cytometry. We found that ZA treatment altered bone responses to PTH. The expression of sfrp4, a Wnt antagonist, was significantly increased in ZA-affected osteocytes. BM EPCs were increased in response to acute PTH but not when treatment was combined with ZA. ZA treatment augmented EPCs in the BM but not in blood which suggests that ZA treatment may have differential effects between the BM and blood. These findings indicate that osteocytes and BM EPCs in mice on ZA treatment respond differently to acute PTH from those not receiving ZA. This may partially explain the mechanisms of previous reports that ZA therapy attenuates the anabolic effect of PTH in bone.